The financing of innovative firms - Bronwyn H. Hall (EIB Papers, 2009)
To what extent are new and/or innovative firms fundamentally different from established firms, and therefore require a different form of financing? The theoretical background for this proposition is presented, and the empirical evidence on its importance is reviewed. Owing to the intangible nature of their investment, asymmetric-information and moralhazard, these firms are more likely to be financed by equity than debt and behave in some cases as though they are cash-constrained, especially if they are small. Recognising the role for public policy in this area, many countries have implemented specific policies to bring the cost of financing innovation more in line with the level that would prevail in the absence of market failures.
Keywords: 330; Forschungskosten; Forschungsfinanzierung; Unternehmensfinanzierung; Forschungs- und Technologiepolitik; Asymmetrische Information; Moral Hazard